Konseling Karier Berbasis Minat Bakat Bagi Disabilitas Netra di Pendowo Kudus - Farida, Farida; Wijaya, Mashadhi; Anggraeni, Widya; ‘Ubudiyah, Farikhatul (Jurnal Bimbingan dan Konseling Islam, 2024)
Everyone has the potential to have a career, including people with visual disabilities. They also have potential, abilities, skills and dreams. This article aims to understand the process of implementing career counseling to improve life skills for people with visual disabilities at the Pendowo Kudus Social Services Center for the Visually Disabled (PPSDN Pendowo Kudus). This research uses a qualitative descriptive method with data collection in the form of observation, interviews and documentation. Data analysis uses data triangulation. The research results show that there are two types of career guidance implemented, namely academic and non-academic. There are efforts to improve life skills that must be mastered, namely maintaining life in society, caring for oneself, and being able to relate interpersonally. From these skills, an attitude of never giving up, self-knowledge, self-concept, and an independent attitude can be instilled for people with visual disabilities. Some of the preferences offered in career counseling are weaving, ecoprint, hanger, doormat, talking computer, massage, Maybank entrepreneurship training, and so on.